2019
DOI: 10.1002/mp.13383
|View full text |Cite
|
Sign up to set email alerts
|

An algorithmic approach to single‐probe Cherenkov removal in pulsed x‐ray beams

Abstract: Purpose: The removal of Cherenkov light in an optical dosimetry system is an important process to ensure accurate dosimetry without compromising spatial resolution. Many solutions have been presented in the literature, each with advantages and disadvantages. We present a methodology to remove Cherenkov light from a scintillator fiber optic dosimeter in a pulsed megavoltage x-ray beam using the temporal waveform across the pulse. Methods: A sample waveform of Cherenkov light can be measured by exposing only the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…However, the long decay time of some scintillators relative to the Cherenkov effect has also inspired solutions for eliminating the Cherenkov interference. For example, the BC-444 scintillator (Saint-Gobain Crystals) was chosen by Archer et al [49] to fabricate a PSFD because of its slow rise and decay time compared to the Cherenkov effect. They applied an algorithm-based temporal Cherenkov removal technique to eliminate Cherenkov interference.…”
Section: Basic Physical Properties Of Scintillatorsmentioning
confidence: 99%
“…However, the long decay time of some scintillators relative to the Cherenkov effect has also inspired solutions for eliminating the Cherenkov interference. For example, the BC-444 scintillator (Saint-Gobain Crystals) was chosen by Archer et al [49] to fabricate a PSFD because of its slow rise and decay time compared to the Cherenkov effect. They applied an algorithm-based temporal Cherenkov removal technique to eliminate Cherenkov interference.…”
Section: Basic Physical Properties Of Scintillatorsmentioning
confidence: 99%
“…In recent work with plastic scintillation dosimeters, temporal kinetic modelling was applied to derive the expected scintillation, S(t), in response to some time dependent dose-rate Ḋ(t) [22]. It was found that the expected scintillation was proportional to the mathematical convolution of the dose-rate as a function of time, Ḋ(t), and an exponential rise and decay that is characteristic of the plastic scintillator [22]. Similarly, the measured rtOSL signal is dependent on a time dependent dose-rate, Ḋ(t), hence the same technique is applicable for rtOSL.…”
Section: Temporal Signal Modellingmentioning
confidence: 99%
“…The stem effect adds to the radioluminescence (RL) signal, producing a bias in the dose rate measurement. Several methods have been put forward to reduce the stem effect, which are useful in different situations 17 . The time‐gated technique is suitable for filtering the short‐lived Cherenkov signal in LINACs when the scintillator features a long decay time of its RL signal of the order of 1 ms 18 .…”
Section: Introductionmentioning
confidence: 99%